The guitar in America : Victorian era to jazz age - Noonan, Jeffrey (American made music series., 2008)
The Guitar in America offers a history of the instrument from America\'s late Victorian period to the Jazz Age. The narrative traces America\'s BMG (banjo, mandolin, and guitar) community, a late nineteenth-century musical and com-mercial movement dedicated to introducing these instru-ments into America\'s elite musical establishments. Using surviving BMG magazines, the author details an almost unknown history of the guitar during the movement\'s heyday, tracing the guitar\'s transformation from a refined parlor instrument to a mainstay in jazz and popular music. In the process, he not only in.